Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.